Proceed With Caution: Using Web-Based Resources for Instructing Students With and at Risk for EBD. (April 2019) - Beahm, Lydia A.; Cook, Bryan G.; Cook, Lysandra
Educators frequently use social media platforms such as Pinterest and Teachers Pay Teachers for guidance on teaching. In this article, we explore reasons why these websites are popular with educators, consider their potential risks and benefits, and provide examples of resources provided on these sites. We recommend that educators first identify and learn the critical elements of effective practices from trustworthy sources and then use sites such as Pinterest and Teachers Pay Teachers to facilitate implementation.